SOCIO-PSYCHOLOGICAL FEATURES OF FORMATION OF THE PROCESS OF THINKING INDEPENDENCE IN ADOLESCENCE - Yuldasheva Malokhat Erkinovna (Journals Park Publishing, 2024)
The article discusses the theoretical foundations for the development of independent thinking in adolescence, which is one of the pressing problems of pedagogy and psychology. The article highlights the unique problems of developing independent thinking in a teenager and the scientific theories of a number of psychologists on this topic.
Keywords: Teenager, thinking, independent thinking, independent thinking, tendency to independence.